2017
DOI: 10.1016/j.agwat.2016.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fertigation effect on photosynthesis, grain yield and water use efficiency of winter wheat

Abstract: Excessive fertilization is common in North China Plain. It is essential to determine the extent to which reduction of nitrogen application rates has little impact on yield and understand its physiological basis. Two seasons of field experiments were conducted in a winter wheat field with three nitrogen (N) fertilization treatments, i.e. N3, traditional N application rates (290 kg N hm-2), N2, ~65% N application rates of N3 (190 kg N hm-2) and N1, ~40% N application rates of N3 (110 kg N hm-2). Yield (Y) and wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(48 citation statements)
references
References 43 publications
13
35
0
Order By: Relevance
“…Thus, high-N fertilizer plots are more likely to be water-deficient if the soil moisture is inadequate, which aggravates the plant's stomatal limitations (1-Ci/Ca) and resulting in reduction of Gs and Pn. Similar findings have been described in wheat (Zhang et al, 2017). Previous studies also pointed out that under soil water-stress, ABA (as the signal carrier) transmitted to the shoot, reducing the Gs and increasing stomatal limitations in the initial drought (Larcher, 2003;Li & Xu, 2014;Yan et al, 2017).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Thus, high-N fertilizer plots are more likely to be water-deficient if the soil moisture is inadequate, which aggravates the plant's stomatal limitations (1-Ci/Ca) and resulting in reduction of Gs and Pn. Similar findings have been described in wheat (Zhang et al, 2017). Previous studies also pointed out that under soil water-stress, ABA (as the signal carrier) transmitted to the shoot, reducing the Gs and increasing stomatal limitations in the initial drought (Larcher, 2003;Li & Xu, 2014;Yan et al, 2017).…”
Section: Discussionsupporting
confidence: 81%
“…In 2016 and 2017, 20 plants were marked prior to the eight-leaf stage (V8). At V8, the tasseling stage (VT), milking stage (R3), and physiological maturity (R6), the three marked plants per plot were selected to measure the net photosynthetic rate (Pn), intercellular CO 2 concentration (Ci), and stomatal conductance (Gs) on the ear leaves (at VT, R3, and R6) or fully expanded leaves at the top of a plant (at V8) using a photosynthesis analyzer system (LI-6400, LI-COR, Lincoln, NE, USA) on a clear sunny day between 9:00 AM and 11:00 AM (Zhang et al, 2017). The same plants were used for measuring the green leaf area at V8, VT, R3, and R6.…”
Section: Photosynthetic Parameters and Leaf Area Indexmentioning
confidence: 99%
“…The application of nitrogen fertilizer can increase tuberous root yield (Kiymaz and Ertek 2015). Previous studies have found that the PNmax can reflect crop yield (Zhang et al 2017a). In our study, the PNmax and root yields for R1 and R2 treatments with the application rates of N2 and N3 were higher than those with N1 (Table 4).…”
Section: Discussionsupporting
confidence: 48%
“…In our results, long-term optimized NPK not only coincided with the maize requirement in different growing stages but also increased N use efficiency while part of nitrogen input was replaced by organic manure (Fig 4B). Zhang et al [35] report that long-term manure application prevents excess N from leaching out and forms a rational sufficient N condition in the topsoil. Optimized chemical fertilization strategies with organic manure can maintain the soil nutrient balance with high use efficiency and lower environmental costs [28,34,36], providing an option for N management in sustainable cropping systems [1].…”
Section: Plos Onementioning
confidence: 99%